Anxiety, depression, trauma-related, and sleep disorders among healthcare workers during the COVID-19 pandemic: A systematic review and meta-analysis. (July 2021) - Marvaldi, Maxime; Mallet, Jasmina; Dubertret, Caroline; Moro, Marie Rose; Guessoum, Sélim Benjamin
Graphical abstract: Highlights: The mental health burden during the COVID-19 crisis is heavy among healthcare workers. This meta-analysis estimated high pooled prevalences of psychiatric conditions. Anxiety, depression and sleep problems were respectively 300 %, 311 %, and 440 %. Estimates of acute and post-traumatic stress were high (56.5 %, 20.2 %). Support interventions are urgent for workers' wellbeing and quality of care. Abstract: Healthcare workers have been facing the COVID-19 pandemic, with numerous critical patients and deaths, and high workloads. Quality of care is related to the mental status of healthcare workers. This PRISMA systematic review and meta-analysis, on Pubmed/Psycinfo up to October 8, 2020, estimates the prevalence of mental health problems among healthcare workers during this pandemic. The systematic review included 70 studies (101 017 participants) and only high-quality studies were included in the meta-analysis. The following pooled prevalences were estimated: 300 % of anxiety (95 %CI, 24.2–37.05); 311 % of depression (95 %CI, 25.7–36.8); 565 % of acute stress (95 %CI - 30.6–80.5); 20, 2% of post-traumatic stress (95 %CI, 9.9–33.0); 44.0 % of sleep disorders (95 %CI, 24.6–64.5). The following factors were found to be sources of heterogeneity in subgroups and metaregressions analysis: proportion of female, nurses, and location. Targeted prevention and support strategies are needed now, and early in case of future health crises.